Regulatory 3′ Untranslated Regions of Bacterial mRNAs - Ren, Gai-Xian; Guo, Xiao-Peng; Sun, Yi-Cheng (Frontiers in Microbiology, 2017)
The untranslated regions (UTRs) of mRNA contain important features that are relevant to the post-transcriptional and translational regulation of gene expression. Most studies of bacterial UTRs have focused on the 5regions; however, 3UTRs have recently emerged as a new class of post-transcriptional regulatory elements. 3UTRs were found to regulate the decay and translation initiation in their own mRNAs. In addition, 3UTRs constitute a rich reservoir of small regulatory RNAs, regulating target gene expression. In the current review, we describe several recently discovered examples of bacterial regulatory 3UTRs, discuss their modes of action, and illustrate how they facilitate gene regulation in various environments.